2018
DOI: 10.1111/crj.12751
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of low‐dose urokinase for the treatment of hemodynamically stable AECOPD patients with acute pulmonary thromboembolism

Abstract: The incidence of PTE in AECOPD patients was 22.9%, especially with higher occurrence rate in severe COPD. Compared with anticoagulation-only therapy, low-dose UK treatment (500 000 IU/day for 5-7 days) could obtain a better efficacy and safety in hemodynamically stable AECOPD patients with acute PTE, corresponding with a higher effective rate (97.2%) and lower adverse events rate (8.3%) respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The results showed that the hospitalization time of these patients at 3–6 months after treatment was shorter than that in the conventional treatment group, and the reduction rate of pulmonary artery thrombosis was higher. Jing et al 59 studied 96 patients with hemodynamically stable AECOPD combined with PE and found that low-dose urokinase (500,000 IU/day, 5–7 days) could improve the effective rate of hospitalization and reduce the incidence of adverse events and mean recurrence time within 1 year, but further clinical studies are needed to confirm this. Inferior vena cava filter implantation (IVC) is a good treatment option for high-risk PE patients.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…The results showed that the hospitalization time of these patients at 3–6 months after treatment was shorter than that in the conventional treatment group, and the reduction rate of pulmonary artery thrombosis was higher. Jing et al 59 studied 96 patients with hemodynamically stable AECOPD combined with PE and found that low-dose urokinase (500,000 IU/day, 5–7 days) could improve the effective rate of hospitalization and reduce the incidence of adverse events and mean recurrence time within 1 year, but further clinical studies are needed to confirm this. Inferior vena cava filter implantation (IVC) is a good treatment option for high-risk PE patients.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…AECOPD is a phenomenon whereby patients with COPD have an aggressive airway obstruction, difficulty breathing, and increased sputum in a short amount of time. Patients with AECOPD have a higher rate of infection with respiratory viruses and atypical clinical manifestations; this is especially true for patients over the age of 65 (18,19). Studies by Dr. Jie and his colleagues have examined the pharmacological action of Chinese medicine against influenza.…”
mentioning
confidence: 99%